A novel approach based on sequence prediction for webpage access - Thon Da, Nguyen; Hanh, Tan (International Journal of Engineering and Technology, 2018)
Predicting the next item of a sequence over a finite alphabet is highly important in Web Mining. This paper presents a solution to improve the performance of sequence prediction; first and foremost, predicting what is the next Web page that will be visited by that user for prefetching the Web page. The proposed approach is how to decrease the complexity of the prediction space. Experimental results on a few real-life datasets show that the time execution of this novel approach is better than that of traditional approaches. Â Â